Orally delivered polycurcumin responsive to bacterial reduction for targeted therapy of inflammatory bowel disease - Hongzhi Qiao; Dong Fang; Jing Chen; Yuan Sun; Chen Kang; Liuqing Di; Junsong Li; Zhipeng Chen; Jun Chen; Yahan Gao (Taylor & Francis Group, 2017)
Inflammatory bowel disease (IBD) such as Crohn's disease and ulcerative colitis is a chronic autoimmune disease affecting nearly five million people worldwide. Among all drug delivery system, oral administration is the most preferable route for colon-specific targeting and the treatment of IBD. Herein, an amphiphilic curcumin polymer (PCur) composed of hydrophilic poly(ethylene glycol) (PEG) and hydrophobic curcumin (Cur) linked by disulfide bond was synthesized and characterized. The sufficient solubility, nano-scaled size and close to the neutral surface potential of PCur lead to preferential accumulation of the active drug in the inflamed regions of the gut. Moreover, PCur showed limited drug release and enhanced robustness under the physiological pH of the gastrointestinal tract (GIT), and a significantly elevated release was observed when responding to a bacterial reduction in the colon. Furthermore, cellular studies confirmed PCur had low cytotoxicity and increased transmembrane permeability, resulting in improved oral bioavailability evidenced by in vivo pharmacokinetics of rats. Finally, with DSS-induced murine model of IBD, we demonstrated that orally administered PCur ameliorated the inflammatory progression in the colon and could protect mice from IBD. In conclusion, it is illustrated that the developed PCur conjugate could potentially be employed as a colon-specific candidate for IBD treatment.